Problematika Dan Rekonstruksi Kepastian Hukum Penanaman Modal Asing Dalam Sistem Hukum Investasi Indonesia Pasca Undang-Undang Cipta Kerja - Emiel Salim Siregar; Syahrizal Aziz Harahap; M. Bryantara Ramadhan; Dwi Silviani; Bima Aslam Anugerah (Pagaruyuang Law Journal, 2026)
Foreign direct investment (FDI) plays a strategic role in driving national economic growth through increased investment, technology transfer, and job creation. To enhance investment competitiveness, the Indonesian government implemented regulatory reforms through the Job Creation Law, which aims to simplify business licensing and strengthen the ease of doing business. However, the implementation of this policy continues to raise various problems related to legal certainty, such as regulatory asymmetry between the central and regional governments, rapid policy changes, and the suboptimal risk-based licensing system through the Online Single Submission (OSS). This study aims to analyze the problems of legal certainty for foreign investment and formulate a legal reconstruction in the Indonesian investment system after the Job Creation Law. The research method used is normative legal research with a statutory and conceptual approach. The results show that legal certainty for investment in Indonesia still faces various obstacles that can affect investor confidence. Therefore, legal reconstruction is needed through regulatory harmonization, strengthening the licensing system, improving institutional quality, and improving investment dispute resolution mechanisms. These efforts are expected to create a stable, fair, and sustainable investment climate in Indonesia.